ECG Workout : Exercises in Arrhythmia Interpretation. - Huff, Jane (Wolters Kluwer Health, 2016)
"Grasp the electrocardiography basics and identify arrhythmias accurately, with the freshly updated ECG Workout, 7th Edition. Fully addressing the most common arrhythmias, this clearly worded text will take you step-by-step through expert ECG tracing interpretation methods, including differentiating among rhythm groups, equipment use, and management protocols. This is the go-to ECG guide for both student training and professional review--perfect for physicians, nurses, medical and nursing students, paramedics, emergency medical technicians, telemetry technicians, and related practitioners. Get a strong grounding in accurate ECG readings with: NEW pull-out arrhythmia summary cards help you interpret end-of-chapter practice strips, NEW and updated advanced cardiac life support (ACLS) guidelines incorporated in each arrhythmia chapter, NEW and updated figures, boxes, tables, and additional practice strips, Updated coverage of all ECG concepts and skills, including: Illustrated anatomy and physiology of the heart, Electrical basis of electrocardiology, Arrhythmia chapters: sinus, atrial, junctional and AV blocks, ventricular and bundle-branch block rhythms--examples, causes, clinical treatments, and practice strips, Step-by-step direction on interpreting rhythm strips, Components of the ECG tracing: waveforms, intervals, segments, complexes, and waveform identification, Discussion of cardiac monitors, lead systems, lead placement, ECG artifacts, and troubleshooting monitor problems, Methods for precise rate calculation, Discussion of cardiac pacemakers: types, indications, function, pacemaker terminology, malfunctions, and pacemaker analysis, with practice tracings. ECG conversion table ensures precise heart rate calculation with plastic pocket version inside back cover. Skillbuilder practice strips--more than 600 life-size ECG tracings: End-of-chapter strips from actual patients, with 3-second indicators for rapid-rate calculation, and answers at back of book. A mix of arrhythmias to help you distinguish among types. Posttest with mix of more than 100 waveform rhythm strips, for student testing or self-evaluation"--Provided by publisher.